Processing of nanolitre liquid plugs for microfluidic cell-based assays - Fukuda, Junji (Sci Technol Adv Mater, 2012)
Plugs, i.e. droplets formed in a microchannel, may revolutionize microfluidic cell-based assays. This study describes a microdevice that handles nanolitre-scale liquid plugs for the preparation of various culture setups and subsequent cellular assays. An important feature of this mode of liquid operation is that the recirculation flow generated inside the plug promotes the rapid mixing of different solutions after plugs are merged, and it keeps cell suspensions homogeneous. Thus, serial dilutions of reagents and cell suspensions with different cell densities and cell types were rapidly performed using nanolitres of solution. Cells seeded through the plug processing grew well in the microdevice, and subsequent plug processing was used to detect the glucose consumption of cells and cellular responses to anticancer agents. The plug-based microdevice may provide a useful platform for cell-based assay systems in various fields, including fundamental cell biology and drug screening applications.